Fiscal dominance and monetary policy effectiveness: Evidence from sub-Saharan Africa - Onyam, Edom Edom; Okoyeuzu, Chinwe R.; Kalu, Ebere U.; Walter, Mboto Helen; John, John Ime; Ukpere, Wilfred Isioma (Edelweiss Applied Science and Technology, 2025)
This study investigated the responsiveness of monetary policy effectiveness in Sub-Saharan African, covering the period 1974-2023. Using P-ARDL bound test approach to analyze the result the findings showed that inflation, real interest rate, exchange rate, debt service payment and government debt are positive and significant function of fiscal dominance, while fiscal dominance had a negative and significant effect on broad money growth in SSA. Based on the result, the study recommended that since policy regime shifts arise endogenously, monetary authorities in sub-Saharan Africa can reduce the risk of a shift to fiscally dominant regime by responding moderately to inflation while making sure they pursue price stability through the application of the Taylor principle.